"Doing the 'Real' Work": How Superintendents' Sensemaking Shapes Principal Evaluation Policies and Practices in School Districts. (January 2021) - Donaldson, Morgaen L.; Mavrogordato, Madeline; Youngs, Peter; Dougherty, Shaun; Al Ghanem, Reem
Almost every state in the United States has revamped its principal evaluation policies since 2009, yet we know little about how they are implemented. Based on interviews and document analysis in 21 small- and medium-sized school districts, we found that superintendents' sensemaking shaped their implementation of policy. Drawing on their beliefs about principals and evaluation and their understanding of their district context, superintendents in lower performing districts reported that they complied with the processes specified in state principal evaluation policies but strayed from state guidelines regarding maintaining a focus on instructional leadership during evaluation. In contrast, superintendents of higher performing districts reported that they implemented evaluation processes loosely but adhered to their state's policy emphasis on instructional leadership. Our findings raise questions about whether the implementation of principal evaluation policies disadvantages principals in lower performing districts. We thus caution against attaching high-stakes consequences such as incentive pay or sanctions to these policies.